2017
DOI: 10.1080/02699206.2017.1312533
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative differences in the lexical knowledge of monolingual and bilingual children on the LITMUS-CLT task

Abstract: While bilingual children follow the same milestones of language acquisition as monolingual children do in learning the syntactic patterns of their second language (L2), their vocabulary size in L2 often lags behind compared to monolinguals. The present study explores the comprehension and production of nouns and verbs in Hebrew, by two groups of 5- to 6-year olds with typical language development: monolingual Hebrew speakers (N = 26), and Russian-Hebrew bilinguals (N = 27). Analyses not only show quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
5
22
2
Order By: Relevance
“…In line with the frequently made observation that bilingual children may lag behind monolingual peers in at least one of their two languages on (expressive) vocabulary, some studies found significant differences between monolinguals and bilinguals on the CLT (Altman, Goldstein & Armon-Lotem, 2017;Hansen et al, 2017). At the same time, other studies have failed to find such a difference, perhaps because they included simultaneous (rather than sequential) bilingual children (Lindgren, 2018), or children with substantially more input in the language of testing than in their other language(s) (Potgieter & Southwood, 2016).…”
Section: Measurementioning
confidence: 64%
“…In line with the frequently made observation that bilingual children may lag behind monolingual peers in at least one of their two languages on (expressive) vocabulary, some studies found significant differences between monolinguals and bilinguals on the CLT (Altman, Goldstein & Armon-Lotem, 2017;Hansen et al, 2017). At the same time, other studies have failed to find such a difference, perhaps because they included simultaneous (rather than sequential) bilingual children (Lindgren, 2018), or children with substantially more input in the language of testing than in their other language(s) (Potgieter & Southwood, 2016).…”
Section: Measurementioning
confidence: 64%
“…The test includes subtests for vocabulary, sentence repetition, comprehension, oral expression, pronunciation and storytelling. Scores were measured against Altman et al’s (2016) adjusted bilingual norms. English was evaluated via the Core Language Score from the CELF-Preschool-2 (Wiig et al, 2004), which is often used to quantify English language performance.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, heritage speakers may perform relatively better in these tasks as they can draw on other strengths for support. Following instructions is also a receptive language task and outcomes may be expected to be more advanced than expressive language tasks (Altman et al, 2017, 2018). In the case of heritage language speakers, a difference of one or more than one standard deviation has been reported (Keller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Information included age of onset of societal language, length of exposure to the societal language calculated as the child’s chronological age minus age of onset, and current exposure to the societal language. As a control language measure, receptive vocabulary was assessed using comprehension subtests of the Hebrew LITMUS CLT task (Altman, Goldstein, & Armon-Lotem, 2017) and the Russian LITMUS CLT task (Gagarina & Nenonen, 2017).…”
Section: Methodsmentioning
confidence: 99%